Novel micellar CB2 receptor agonist with anti-inflammatory action for treating corneal alkali burns in a mouse model - Thathapudi, Neethi C.; Groleau, Marc; Degué, Delali S.; Aghajanzadeh Kiyaseh, Mozhgan; Kujawa, Piotr; Soulhi, Fouzia; Akla, Naoufal; Griffith, May; Robert, Marie-Claude (Frontiers in Pharmacology, 2023)
Moderate corneal alkali burns such as those sustained from accidental exposure to household chemicals are treated with topical corticosteroids. Side effects include increased intraocular pressure and slowing of wound healing. Here, a cannabinoid receptors 2 (CB2r) agonist, TA-A001, that is involved in wound healing is encapsulated with a polymeric micelle comprising polyvinylpyrrolidone: polylactide block copolymers referred to as SmartCelle™ to allow delivery of the very hydrophobic drug. In mouse corneas that received moderate alkali burns, doses of 0.25% and 0.5% TA-A001 allowed for faster wound closure. However, the higher 0.5% dose also induced unwanted neovascularization. By comparison, burned corneas treated with the corticosteroid, prednisolone, showed slower healing as well as swelling of the corneas. Although 0.25% TA-A001 appeared to produce the most-optimal responses, this dose resulted in marked expression of the macrophage chemoattractant protein, MCP-1. However, there was also an increase in CD163 positive stained M2 anti-inflammatory macrophages in the TA-A001 corneas. TA-A001 treated corneas showed the presence of sensory nerve fibers throughout the corneal epithelium including the superficial cell layers as did Substance P staining. We found that TA-A001 at the 0.25% doses was able to modulate inflammation resulting from a moderate alkali burn to the cornea and with more extensive testing, might prove to be a potential alternative to corticosteroids for treating alkali burns or other causes of corneal inflammation.